Adat perpatih: its practices and relevance in contemporary Malaysian society / Siti Alimah Ali ... [et al.] - Ali, Siti Alimah; Sy. Zaharim Helmi, Sh. Zamirah; Abd Rahman, Nurdiyana; Mohd Ali, Nur Haliza (2005)
This research will focus on the problems arising in administration, marriage, and property distribution which seems to be inconsistent or irrelevant in these present days. It will be conducted to determine the extent to which its practices are relevance in the present situation. Adat laws are extended to the aspects of political, economical, inheritance, marriage, and judicial life. The failure of the society to understand several concepts of the adat has led them to judge the adat as not relevant in today society and this research therefore is to provide maximum disclosure of the very unique of the said adat to society at large. In the process of collecting data, basic reading on Adat Perpatih will be done through the relevant secondary sources such as books, textbooks and extracts from the internet. Application of primary source is through our own observations. This research relies on the primary data as well. This data will be collected by conducting interviews with experts and by distributing questionnaires. This research is necessary to test the relevancy of Adat Perpatih in this modern society. It will provide some options to amend or change the adat law to fit the modern society. The adat that is not relevant can be changed so it can be in line with ordinary laws.